Aktivitas Antibakteri Ekstrak Etanol Daun Mangga (Mangifera indica L. var. Arum Manis) Terhadap Bakteri Streptococcus pyogenes - Hilda, Nabila Husnaini; Mulangsri, Dewi Andini Kunti (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Mango leaves contained active compounds such as tannins, flavonoids, phenols, and saponins. Its absorbed in ethanol extract and acted as antibacterial against Streptococcus pyogenes bacteria. The purpose of this study was known active compounds and the antibacterial activity against Streptococcus pyogenes bacteria of ethanol extract of mango leaves (Mangifera indica L. var. Arum Manis). Ethanol extract of arum manis mango leaves (EEAML) was obtained by maceration method with 96% ethanol solvent that was tested for phytochemical screening such as alkaloid, flavonoid, phenolic, tannin and saponin. Serial of EEAML concentration has made at 5, 7.5, 10 (%) with DMSO solvent that was tested for antibacterial activity by disk diffusion method and gradually incubated at 37° C for 48 hours then at room temperature for up to 60 hours in anaerobic jars. Positive and negative control were used erythromycin 15 µg/disk and DMSO solvent respectively. The data, that resulted from phytochemical screening test and antibacterial activity test, was analyzed by descriptively. The results of phytochemical screening test of EEAML was contained as flavonoids, phenolics, tannins, and saponins.The EEAML was showed antibacterial activity all of concentrations with zone of inhibition diameters values at 13.03 mm, 16.83 mm and 18.27 mm.